2014
DOI: 10.3109/02699052.2014.888771
|View full text |Cite
|
Sign up to set email alerts
|

Screening for lifetime concussion in athletes: Importance of oculomotor measures

Abstract: The study provides a relatively sensitive screening tool to assess the probability of previous concussion(s) in an athlete. This model may allow athletic personnel to address in a timely manner the risks associated with repeat concussions and to develop individualized concussion management protocols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 46 publications
0
24
3
Order By: Relevance
“…Accommodation was addressed in 5 studies. 32,33,35,36,44 Deficits in accommodation were found in all studies. For example, Green et al 35 found a range of deficits in static and dynamic accommodation in individuals with mTBI using specific optometric tests conducted by an optometrist.…”
Section: Vergence and Accommodationmentioning
confidence: 80%
See 4 more Smart Citations
“…Accommodation was addressed in 5 studies. 32,33,35,36,44 Deficits in accommodation were found in all studies. For example, Green et al 35 found a range of deficits in static and dynamic accommodation in individuals with mTBI using specific optometric tests conducted by an optometrist.…”
Section: Vergence and Accommodationmentioning
confidence: 80%
“…46,47 Study designs were largely exploratory or preliminary (pilot) and were appraised at class III (N = 9) * or class IV (N = 11). [31][32][33]35,36,38,40,[42][43][44][45] The majority of designs were case-control (N = 12), 14,29,30,[33][34][35][36][37][38][39]46,47 caseseries (N = 3), 40,41,44 prospective cohort design (N = 4), 31,42,43,45 and retrospective chart review (N = 1). 32 Oculomotor-based vision was measured by eye tracker technology (N = 8), 22,[29][30][31]34,38,46,47 comprehensive eye examination by an optometrist (N = 6), 32,33,35,36,39,44 the King-Devick test (N = 5), [40][41][42][43]45 electro-oculography (N = 1), ...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations